ForceX and forceR: A mobile setup and r package to measure and analyse a wide range of animal closing forces. Issue 9 (21st June 2022) - Rühr, Peter T.; Blanke, Alexander
Abstract: Animal closing forces such as bite and pinch forces may determine access to food and mates and are therefore important performance metrics related to fitness. Previous measurement setups to obtain in vivo closing force data were often custom‐made for each study, hampering comparisons among different studies. Additionally, most setups were limited in the size range of taxa they can measure, especially towards smaller species. We introduce forceX, a closing force measurement setup that allows the measurement of a large range of taxa with a great size variety, and forceR, an accompanying software package to analyse the data. forceX is mostly based on off‐the‐shelf components and 3D‐printed or metal‐turned parts. Gape distance can be modified during measurements, and replaceable tip elements of varying thickness allow a minimal gape distance of ~0.3 mm. Thus, forceX allows closing force measurements of smaller species, while still being able to measure medium‐sized animals as well. Animals are not harmed during the measurements, and the whole setup can be assembled within minutes, is battery‐powered, light‐weight and transportable. The forceX system is able to accurately (linear regression of measured forces vs. control forces: p  < 0.001; R 2  > 0.999; n  = 1, 609) and reproducibly (mean of absolute relative errors = 0.93%; SD  = 1.42%; n  = 1, 609) measure forces across three orders of magnitude (0.01–10 N). Importantly, whole force curves, instead of just maximum force values are stored, and forceR allows extracting individual peak shapes from these curves to facilitate the statistical analysis of both maximum force values and peak curve shapes. forceX and forceR facilitate rapid and minimally invasive in vivo measurements and analyses of closing forces in animals across a wider range of taxa than previously possible, including, for example, many small species of the megadiverse insects. The system allows studying the characteristics, predictors, and evolution of both maximum closing forces and force curve shapes.